Complete the Expression: (9×2)^(3x) Mathematical Pattern

Question

Insert the corresponding expression:

(9×2)3x= \left(9\times2\right)^{3x}=

Video Solution

Solution Steps

00:00 Simplify the following problem
00:04 In order to open parentheses with a multiplication operation and an outside exponent
00:08 Raise each factor to the power (N)
00:11 We will apply this formula to our exercise
00:14 Note that all the factors in the multiplication operation are raised to the same exponent (N)
00:17 Therefore, we will raise each factor to this power (N)
00:20 This is the solution

Step-by-Step Solution

To solve this problem, we'll apply the power of a product rule for exponents:

  • Identify that (9×2)3x(9 \times 2)^{3x} is a product of two numbers 99 and 22 raised to the same power 3x3x.
  • Apply the power of a product rule: (ab)n=an×bn(ab)^n = a^n \times b^n.
  • In our case, a=9a = 9, b=2b = 2, and n=3xn = 3x.
  • Thus, (9×2)3x=93x×23x(9 \times 2)^{3x} = 9^{3x} \times 2^{3x}.

Therefore, the expression (9×2)3x(9 \times 2)^{3x} simplifies to 93x×23x 9^{3x} \times 2^{3x} .

Answer

93x×23x 9^{3x}\times2^{3x}